Geotechnical Frontiers 2025 - Soil Characterization and Improvement - Beauregard Melissa S; Budge Aaron S (American Society of Civil Engineers (ASCE), 2025)
Selected papers from Geotechnical Frontiers 2025, held in Louisville, Kentucky, March 2-5, 2025. Sponsored by the Geosynthetic Materials Association, Advanced Textiles Association, and the Geo-Institute of ASCE. This Geotechnical Special Publication contains 61 peer-reviewed papers on soil characterization and improvement. Topics include: engineering geology and site characterization; geophysical engineering; rock mechanics; soil improvement; soil properties and modeling; and unsaturated soils. GSP 368 will be of interest to geotechnical engineers, researchers, contractors, and other geoprofessionals working with various soil types and sites.